Odpowiedzi

2009-11-12T17:15:11+01:00
3m+n=9
2m-5n=-11
n=-3m+9
2m-5n=-11
n=-3m+9
2m-5*(-3m+9)=-11
n=-3m+9
2m+15m-45=-11
n=-3m+9
17m=34/:17
n=-3m+9
m=2
n=-3*2+9
m=2
n=3
W drugim przykładzie niestety nie pomogę.
2009-11-12T17:21:38+01:00
1) 3m+n=9
2m-5n= -11
{
n=9-3m
2m-5(9-3m)= -11
{
n= 9-3m
2m-45+15m= -11
{
n=9-3m
17m= -11+45
{
n= 9-3m
17m=34 |:17
{
n= 9-3m
m=2
{
n= 9-3*2
m=2
{
n= 3
m=2

2) 4a-2=9
3a+7b=1,5
{
4a=9+2
3a+7b=1,5
{
4a=11 |:4
3a+7b= 1,5
{
a=2,75
3*2,75 + 7b = 1,5
{
a= 2,75
8,25 +7b=1,5
{
a=2,75
7b= 1,5 - 8,25
{
a= 2,75
7b= -6,75 |:7
{
a=2,75
b w zaokrągleniu 0,9
Najlepsza Odpowiedź!
2009-11-12T17:27:05+01:00
A.
3m +n = 9
2m - 5n = -11

n = 9 - 3m
2m - 5(9 - 3m) = -11

n = 9 - 3m
2m - 45 + 15m = -11

n = 9 - 3m
17m - 45 = -11

n = 9 - 3m
17m = -11 + 45

n = 9 - 3m
17m = 34 / :17

n = 9 - 3m
m = 2

n = 9 - (3*2)
m = 2

n = 3
m = 2

B.
4a - 2 = 9
3a + 7b = 1.5

4a = 9 + 2 / : 4
3a + 7b = 1.5

a = 2.75
3 * 2.75 +7b = 1.5

a = 2.75
8.25 + 7b = 1.5

a = 2.75
7b = 1.5 - 8.25

a = 2.75
7b = -6.75 / : 7

a = 2.75
b = -1 (w przybliżeniu)